Function of metals and supports on the hydrodeoxygenation of phenolic compounds - Deepa, Ayillath K.; Dhepe, Paresh L. (ChemPlusChem, 2014)
Hydrodeoxygenation (HDO) is an important process for removing oxygen from lignin-derived phenolic monomers to obtain chemicals that can be used as fuel or fuel additives. A systematic study is performed to check the effects of supports (acidic, neutral, basic) and noble metals (Pd, Pt, Ru) on the HDO of phenol, guaiacol, and eugenol. Evaluation of the combinations of metals and supports under the similar reaction conditions shows that the metals supported on a highly acidic support (SiO2-Al2O3) yield complete hydrogenation products with the possibility of C[BOND]O bond cleavage to achieve a real HDO activity, whereas on a mildly acidic support (gamma-Al2O3), a complicated product distribution is achieved, and neutral (C) and basic (HT) supports give restricted hydrogenation activity but yield the products with very high selectivity. On the basis of the results, reaction pathways are suggested and deliberated. The catalysts show reproducible activity in recycle runs. The catalysts are characterized by various techniques (XRD, TEM, TPD, ICP-OES) to establish the catalyst activityproperty relationship.

Direct production of furfural in one-pot fashion from raw biomass using bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Hossain, Shahriar A.; Islam, Tofazzal; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. W. (Scientific Reports, 2017)
The conversion of raw biomass into C5-sugars and furfural was demonstrated with the one-pot method using Bronsted acidic ionic liquids (BAILs) without any mineral acids or metal halides. Various BAILs were synthesized and characterized using NMR, FT-IR, TGA, and CHNS microanalysis and were used as the catalyst for raw biomass conversion. The remarkably high yield (i.e. 88%) of C5 sugars from bagasse can be obtained using 1-methyl-3(3-sulfopropyl)-imidazolium hydrogen sulfate ([C3SO3HMIM][HSO4]) BAIL catalyst in a water medium. Similarly, the [C3SO3HMIM][HSO4] BAIL also converts the bagasse into furfural with very high yield (73%) in one-pot method using a water/toluene biphasic solvent system.

ffects of cations, anions and H+ concentration of acidic ionic liquids on the valorization of polysaccharides into furfural - Matsagar, Babasaheb M.; Dhepe, Paresh L. (New Journal of Chemistry, 2017)
The valorization of hemicellulose into valuable chemicals, such as C5 sugars and furfural, in a one-pot fashion is crucial. In this work, acidic ionic liquids in the presence of water showed high yields of C5 sugars (>80%) with >99% conversion of hemicelluloses at 160 degrees C. With a water + toluene biphasic solvent system, within 4 h, an 85% furfural yield was obtained directly from hemicellulose in a one-pot fashion using a catalytic amount of 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate. It was seen that Bronsted acidic ionic liquids (BAILs) perform better than solid acid [Faujasite and Mordenite zeolites; ion exchange resin, Amberlyst-15] and mineral catalysts [HCl and H2SO4]. The higher activity of BAILs compared to solid acids and mineral acids was correlated to the Hammett acidity function (Ho) and ion-dipole type of interactions. The catalysts were characterized using NMR (H-1 and C-13), elemental analysis and TGA to confirm that they were stable under reaction conditions and were thus recyclable.

Effect of structural properties of organosolv lignins isolated from different rice husks on their liquefaction using acidic ionic liquids - Singh, Sandip K.; Dhepe, Paresh L. (Clean Technologies and Environmental Policy, 2018)
Lignin is the only naturally available sustainable resource of aromatic compound on the Earth. Depending on the properties of lignin and the reaction conditions employed for the liquefaction, it is observed that the product distribution alters. Since ionic liquids (ILs) are considered as green and have tuneable properties, in the current work, imidazolium-based acidic ILs were employed to liquefy organosolv lignins derived from different varieties of rice husks. When liquefaction was carried out at 120 A degrees C for 1 h 36% yield for EtOAc- and DEE-soluble products with high mass balance (97 +/- 3%) was observed. The detailed characterisations of lignins and organic solvent-soluble products were done by variety of techniques [GC-MS, FT-IR, UV-Vis, 2D (HSQC) NMR], and based on this, the correlation between activity and properties of catalyst and lignin was established. Depolymerisation of organosolv lignin (derived from three rice husks) into aromatic product was done, and experimental correlation studies were performed in both.

Efficient method for cyclopentanone synthesis from furfural: understanding the role of solvents and solubility in a bimetallic catalytic system - Dohade, Manisha; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
The platform chemical, furfural (FAL), is obtained from C5 stream of biomass, and effective conversion into various chemicals including cyclopentanone (CPO) would find many industrial applications. It is desirable to convert FAL to CPO under low H-2 pressure with high selectivity. In the current work, bimetallic catalysts with Pt as the base metal supported on carbon are evaluated in the synthesis of CPO using a biphasic solvent system. By tuning the solvent ratio, with toluene/water (3:4 v/v), 75% yield of CPO is achieved under 1 MPa H-2 at 180 degrees C. The difference in solubility of the substrate, intermediates and products, along with the optimum ratio of Pt and Co metals plays a crucial role in achieving better yields.

Experimental evidences for existence of varying moieties and functional groups in assorted crop waste derived organosolv lignins - Singh, Sandip K.; Dhepe, Paresh L. (Industrial Crops and Products, 2018)
Isolation of organosolv lignins (ORGLs, water:ethanol, 180 degrees C, 1 h, 93 +/- 5% mass balance) from various lignocellulosic materials like rice husk (RH), wheat straw (WS), bagasse (BG) & wood chips (WC) was done and experimental evidences are provided to perceive the differences in the structures of isolated lignins. To achieve this on bulk level, lignins were characterized by XRD, GPC, TGA & elemental analysis and on molecular level using UV-vis, ATR, 1D/2D HSQC NMR techniques. Besides isolated lignins, crop wastes and pulps were also characterized to divulge details on their properties. It was revealed that lignins have varying concentrations of sinapyl (S), coniferyl (G) and p-coumaryl alcohols (H) and tricin (T) moieties. While, Tricin (T) type lignin moieties are observed only in RH and WS derived lignins, RH derived lignin has higher concentration of side chains than other isolated lignins. Additionally, it is discovered that most lignins have G as main moiety.

Glucose isomerization catalyzed by bone char and the selective production of 5-hydroxymethylfurfural in aqueous media - Matsagar, Babasaheb M.; Van Nguyen, Chi; Hossain, Md. Shahriar A.; Islam, Md. Tofazzal; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. -W. (Sustainable Energy & Fuels, 2018)
The selective production of 5-hydroxymethylfurfural (HMF) is important, and it is difficult with glucose substrates in a water solvent. Here we demonstrate a selective method for glucose-to-HMF conversion using the combined catalysis of bone char and 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate acidic ionic liquid catalysts with a high HMF selectivity (54%) in water.

High surface area nanoporous carbon derived from high quality jute from Bangladesh - Khan, Junayet Hossain; Lin, Jianjian; Young, Christine; Matsagar, Babasaheb M.; Wu, Kevin C. W.; Dhepe, Paresh L.; Islam, Md Tofazzal; Rahman, Md Mahbubur; Shrestha, Lok Kumar; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; et al. (Materials Chemistry and Physics, 2018)
We report an economically viable and environment-friendly strategy for the preparation of nanoporous carbon (NC) from jute which is one of the most abundant natural fibers produced in Bangladesh and some South Asian countries. Nitrogen adsorption-desorption isotherms, X-ray diffraction, Raman spectroscopy, UV spectroscopy, and scanning/transmission electron microscopy were performed to characterize the obtained NC. Three different types of jute-derived NCs have been synthesized at three different temperatures, 700 degrees C, 800 degrees C and 900 degrees C. The NC prepared at 800 degrees C resulted in a high surface area (981 m(2) g(-2)) and was associated with the retention of the original fibrous shapes. This study shows a promising future for jute as a natural precursor for NCs for a myriad of applications ranging from water purification to gas separation to energy conversion and storage.
Keywords: Adsorbents; Graphitization; Jute; Nanoporous carbons; porous materials

KLTL-MCM-41 micro-mesoporous composite as a solid base for the hydrogenation of sugars - Tangale, Nilesh P.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
An approach to the synthesis of KLTL-MCM-41 micro-mesoporous composites of varying SiO2/Al2O3 molar ratio (20-8) was designed by following green technology. The synthesis was based on the recycling of waste mother liquor containing preformed KLTL zeolite crystals and unutilized reagents. The micro-mesoporous composites consist of KLTL zeolite crystals preformed through hydrothermal treatment in the first step. In the second step, the siliceous mother liquor was transformed into mesoporous MCM-41. The physico-chemical properties of the KLTL-MCM-41 micro-mesoporous composites were determined by PXRD, ICP-OES, FTIR, CO2-TPD, Al-27 MAS-NMR, TEM-EDX, HRTEM, and N-2 adsorption-desorption measurements. The mesopores properties of the KLTL-MCM-41 composites depended on the SiO2/Al2O3 molar ratio. The characterization results led to the following conclusions with decreasing SiO2/Al2O3 molar ratio: 1) decreasing order of the mesophase, 2) decreasing wall thickness of the mesopores, and 3) decreasing BET surface area and pore volume. Al-27 MAS-NMR spectra showed that only tetrahedrally coordinated aluminium was contained in zeolite KLTL. Moreover, the total amount and the strength of the basic sites of the KLTL-MCM-41 micro-mesoporous composites owing to the exchangeable potassium content (Al/K ratio approximate to 1) decreased in the order: 8 MMC > 10 MMC > 15 MMC > 20 MMC. The catalytic activity of the synthesized micro-mesoporous samples as a solid base was tested for the hydrogenation of xylose to sugar alcohols

Novel synthesis of immobilized bronsted- acidic ionic liquid: application in lignin depolymerization - Singh, Sandip K.; Dhepe, Paresh L. (Chemistryselect, 2018)
Designing of efficient catalyst for the valorization of lignin is a topic of long neglect due to intrinsic properties of lignin. We show designing of an efficient, stable and recyclable Immobilized-Bronsted acidic ionic liquid (I-BAIL), which was further used as a solid acid catalyst for the depolymerization of lignin. The synthesized I-BAIL catalyst with sulfonic acid (-SO3H) groups was found to be stable until 250 degrees C and has 42.2 wt.% loading of BAIL anchored on silica framework. The detailed characterization (elemental, Thermogravimetric analysis, Fourier transformation-infrared, Nuclear magnetic resonance) of catalyst disclosed formation of strong covalent bond between Si and carbon of BAIL, which in turn is responsible for achieving a stable catalyst. The catalyst could successfully depolymerize range of lignin substrates with high molecular weight (60000 Dalton) at 200(degrees)C in 1 h to achieve 90% yield of tetrahydrofuran soluble products with good mass balance. The formation of products and correlation of products with lignin was achieved with the help of Nuclear magnetic resonance, gel permeation chromatography, gas chromatography, gas chromatography-mass spectrometry, high performance liquid chromatography etc.

Altering the O/C ratio of lignin derived monomers without sacrificing atom efficiency - Singh, Dheerendra; Dhepe, Paresh L. (ChemistrySelect, 2019)
Synthesis of platform and fuel grade chemicals from lignin without losing atom efficiency and lowering O/C ratio is a challenge in a bio-refinery concept. In this work, we report solid acid catalysed alkylation of lignin derived variety of monomers such as guaiacol, veretrole, phenol, anisole, and catechol using numerous alcohols as alkylating agents. Results elaborate that the type of acidity and structure of catalyst play important role in achieving higher dialkylated products (DAP). With 85% conversion of guaiacol, 30.9% DAP formation was achieved at 250 degrees C within 2 h. A unique substrate adsorption study on the catalyst surface and effect of solubility of substrates on the activity of catalyst is evaluated. Catalyst was observed to be recyclable with marginal loss in the activity due to handling error.
Keywords: Alcohols; Alkylation; lignin; Monomers; solid acid catalyst; Up-gradation

Depolymerization of lignin using a solid base catalyst - Chaudhary, Richa; Dhepe, Paresh L. (Energy & Fuels, 2019)
Lignin extraction from lignocellulosic biomass has attracted considerable attention for an alternative production of sustainable fuels and chemicals. We report the lignin isolation from coconut coir using Klason, organosolv, and soda methods and the depolymerization of isolated lignin to value-added chemicals using a solid base catalyst. The yield of isolated lignin by the Klason method was found to be about 4 to 6 times higher than that by other methods. The structure of isolated Klason lignin (CC-KL), organosolv lignin (CC-ORGL), and soda lignin (CC-SL) was studied using attenuated total reflection (ATR), NMR, microanalysis, and so forth. The monomer molecular formula derived from microanalysis suggested that coir lignin is rich in guaiacyl units. ATR and C-13 NMR clearly indicate that CC-ORGL contains more C-C bonds compared to CC-KL and CC-SL. Subsequently, these isolated lignins were depolymerized over a solid base catalyst (NaX) under atmospheric pressure. CC-SL shows a high yield of aromatic products (28%) compared to CC-ORGL and CC-KL. In order to develop a sustainable future technology, one-pot depolymerization of coconut coir was performed which resulted in a high yield (64%) of aromatic products.

Formic-acid-induced using recyclable-ionic liquids as catalysts for lignin conversion into aromatic co-products - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2019)
Lignin has been widely named as a sustainable and renewable bioresource of energy, fuels, chemicals and materials, particularly phenolic chemicals production on Earth. These bio-derived compounds are in great potential need of biorefinery to valorize complete plant biomass. Lignin depolymerization showed a great promise approach to convert into low molecular aromatic products. In this report, high molecular weight (54,000 Da) lignin depolymerization into maximum yields (87%), (>= 95 +/- 6% mass balance) using a formic acid along with dual (-SO3H) functionalized imidazole-based recyclable (4 times) Bronsted acidic ionic liquids (BAILs) as catalysts have been investigated in H2O-CH3OH (1:5, v/v) at 120 degrees C for 1 h. The structural correlations between the lignin and aromatic products were studied by bulk (CHNS, GPC, etc.) and molecular (UV-Vis, FT-IR, NMR (1D/2D) levels experimental techniques. Additionally, the identification of aromatic products was carried out by applying HPLC, GC and GC-MS techniques. Graphic Addition of a formic acid into Bronsted acidic ionic liquids improved the catalytic efficiency significantly for lignin depolymerization into 87% low molecular weight aromatic products. [GRAPHICS] .
Keywords: Bulk and molecular levels analysis; depolymerization; Dual functionalized ionic liquids; Formic acid; lignin

Lignin conversion using catalytic ionic liquids: understanding the role of cations, anions, and hammett acidity functions - Singh, Sandip K.; Dhepe, Paresh L. (Industrial & Engineering Chemistry Research, 2019)
Because it is undisputable that lignin depolymerization is a must to make the biorefinery concept economically feasible, several efforts are put toward it; however, a lot of catalyst designing is required to achieve efficient depolymerization activities. In this work, we show a systematic approach in the synthesis and characterization of ionic liquids (ILs) with varying combinations of cations (imidazole, benzimidazole, phosphonium, and ammonium) and anions (HSO4, PTS (p-toluenesulfonate), Cl, H2PO4, SnCl3, FeCl4, and CuCl3) for the depolymerization of lignin into low-molecular weight aromatic fractions (<220 g/mol) under mild reaction conditions (120 degrees C, 1 h, ambient pressure). In a methodical approach, effects of various reaction parameters such as temperature (70-170 degrees C), time (15-360 min), pressure (N-2, 0.5-3 MPa), solvents and substrate, and so forth were studied to achieve best activity. Among all the catalysts, IL with the imidazolium cation and HSO4 as the anion showed best activity (78% yield). Subsequent to depolymerization, three aromatic monomers (5 wt % pure vanillin) were isolated using flash column chromatography. These aromatic monomers were characterized using gas chromatography (GC), GC-mass spectrometry, and NMR techniques for their purity. Hammett acidity functions (H-0) of ILs were measured using UV-vis photo-spectroscopy, and values are correlated with lignin depolymerization results. Lignin and tetrahydrofuran-soluble products were thoroughly characterized using assorted physicochemical techniques such as NMR (H-1 and C-13), gel permittivity chromatography, thermogravimetric analysis, and so forth. The catalyst was recycled up to six runs and showed similar results in consecutive reactions.

Carbon supported size-controlled ru catalysts for selective levulinic acid hydrogenation into γ-valerolactone - Simakova, Irina L.; Demidova, Yuliya S.; Simonov, Mikhail N.; Niphadkar, Prashant S.; Bokade, Vijay V.; Devi, Nandini; Dhepe, Paresh L.; Murzin, Dmitry Yu (Journal of Siberian Federal University-Chemistry, 2020)
Liquid phase levulinic acid hydrogenation into γ-valerolactone in 1,4-dioxane as a solvent (165°C, 20 bar) was studied over a range of Ru monometallic catalysts using mesoporous carbon material Sibunit as a support. In addition to the catalyst prepared by impregnation with RuCl3∙nH2O (0.1 M) followed by reduction in H2, size-controlled Ru(NPs)/Sibunit catalysts were synthesized by immobilization of polyvinylpyrrolidone (PVP) stabilized Ru nanoparticles (NPs) (dRu=2.4 nm). Сarbon supported colloidal Ru NPs were not studied earlier in levulinic acid hydrogenation. Activity of colloidal Ru(NPs)/Sibunit catalysts was found to be lower than that of impregnated Ru/Sibunit which could be attributed to hampering effect of PVP. However, colloidal Ru(NPs)/Sibunit purified by thermal treatment in air (180°C) followed by reduction in H2 (400°C) exhibited the same activity as impregnated one yielding 93% γ-valerolactone at 100% levulinic acid conversion. Applicability of supported PVP-assisted colloidal Ru NPs in hydrogenation of levulinic acid illustrates a potential to prepare more efficient catalysts for this reaction with a desired particle size. The catalysts were characterized by TEM, XRF, and N2 physisorption to compare their physical chemical properties.

Understanding the influence of alumina supported ruthenium catalysts synthesis and reaction parameters on the hydrodeoxygenation of lignin derived monomers - Singh, Dheerendra; Dhepe, Paresh L. (Molecular Catalysis, 2020)
Up-gradation of lignin derived monomers to value-added and fuel grade products is important to make overall bio-refinery process economical. Although, few studies are devoted on this work yet, systematic study on commercially viable (low loading of metal, recyclable catalyst, mild conditions, high selectivities etc.) is scarce and typically done under harsh conditions. Herein, we report, the methodical effect of support (SiO2, Al2O3 (acidic, basic and neutral), SiO2-Al2O3) on the hydrodeoxygenation (HDO) of lignin derived various monomers, guaiacol, veretrol, eugenol, phenol using very low loading (0.5 wt%) Ru catalyst. Very high yield (82%) of cyclohexanol from guaiacol could be achieved in presence of cyclohexane as a solvent and Ru/Al2O3-Acidic catalyst at 225 degrees C and under 1 MPa H-2 pressure. The detailed study on the effect of solvent, stability and adsorption of reactant & products etc. is done and it was observed that products are more prone to adsorb and undergo further reactions. The complete characterization of fresh and spent catalysts revealed that lower catalyst reduction temperature and presence of Ru in partially higher oxidation state proved by XPS, helps in enhancing the cyclohexanol formation. Subsequently, role of Ru particle size and support on the activity was also investigated.
Keywords: Cyclohexanol; Hydrodeoxygenation; lignin; reaction pathway; supported metal catalyst

Efficient catalytic transfer hydrogenation-hydrodeoxygenation of lignin derived monomers: investigating catalyst properties-activity correlation - Singh, Dheerendra; Dhepe, Paresh L. (Catalysis Communications, 2021)
Reduction of O/C ratio of lignin derived monomers via hydrodeoxygenation (HDO) pathway is conventionally furnished using molecular hydrogen under severe conditions. Nonetheless, due to a prerequisite to accomplish HDO through commercially attractive methodology we report, HDO reactions of various phenolic compounds via catalytic transfer hydrogenation (CTH) pathway using very low loading of Ru (0.5 wt%) on neutral and acidic Al2O3 under nitrogen atmosphere. With guaiacol as a substrate, 74% cyclohexanol yield at 225 degrees C in the presence of IPA is realized. Bi-functionality of metal state, acidity of support and nature of alcohol are perceived to be responsible for the variation in activity.
Keywords: Catalytic transfer hydrogenation (CTH); Cyclohexanol; Hydrodeoxygenation; lignin; Supported metal catalysts

Elucidating the effect of solid base on the hydrogenation of C5 and C6 sugars over Pt–Sn bimetallic catalyst at room temperature - Tathod, Anup P.; Dhepe, Paresh L. (Carbohydrate Research, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Conversion of sugars into <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/sugar-alcohols" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about sugar alcohols from ScienceDirect's AI-generated Topic Pages">sugar alcohols at room temperature with exceedingly high yields are achieved over Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst in the presence of calcined <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/hydrotalcite" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about hydrotalcite from ScienceDirect's AI-generated Topic Pages">hydrotalcite. pH of the reaction mixture significantly affects the conversion and selectivity for sugar alcohols. Selection of a suitable base is the key to achieve optimum yields. Various solid bases in combination with Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalysts were evaluated for hydrogenation of sugars. Amongst all combinations, the mixture (1:1 <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">wt/wt<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) of Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and calcined hydrotalcite showed the best results. Hydrotalcite helps to make the pH of reaction mixture alkaline at which sugar molecules undergo ring opening. The sugar molecule in open chain form has <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/carbonyl-group" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about carbonyl group from ScienceDirect's AI-generated Topic Pages">carbonyl group which can be polarized by Sn in Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Pt facilitates the hydrogenation. In the current work, effect of both; solid base and Sn as a promoter has been studied to improve the yields of sugar alcohols from various C5 and C6 sugars at very mild reaction conditions.
Keywords: Bimetallic catalyst; Hydrogenation; Hydrotalcites; Sugar; Sugar alcohols

Upgrading lignin derived monomers over basic supported metal catalysts - Chaudhary, Richa; Dhepe, Paresh L. (Fuel, 2021)
Catalytic upgradation of aromatic monomers derived from lignin depolymerization is of high interest for the production of sustainable fuels and chemicals. Basic support has potential to provide advantages of better substrate-support interaction and reduced coke formation. Hence, we report the effect of various basic supports for metal catalysts (Pt, Pd, Ru) on the upgradation of phenol, guaiacol and eugenol. The complete hydrogenation product is achieved due to the strong interaction of the substrate with catalyst. Phenol is converted (55%) into cyclohexanol (49% yield) with low loading of Pt catalyst (1 wt%), supported by the higher TON of 1 wt% Pt/NaX (TON = 14844) than 3 wt% Pt/NaX (TON = 5128). Effect of basic support with moderate (NaX) and strong (CHT) basic strengths are corelated for the higher cyclohexanone formation. Presence of strong basic sites and higher TON of 3 wt% C-HT (TON = 6806) directs the significant substrate-support interaction. Catalytic activity and recyclability are supported by the comparable performance of recycle runs and characterizations of the fresh and spent catalysts.
Keywords: aromatic monomers; Hydrogenation; lignin; Solid bases; supported metal catalyst; Upgradation

Alpha-, beta- and gamma-cellulose quantification and two-stage concentrated-dilute acid lignin recovery from three rice husks: lignin characterization and depolymerization - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2022)
Investigations on the compositional analysis of lignocellulosic materials and their properties upon recovery are essential to be studied in order to examine the effects of recovery method, their dependency on the substrate, etc. In this work, three rice husks (RHs) samples were subjected for alpha-, beta- and gamma-cellulose, pentosan, and silica quantifications. Correlations between the source of biomass, lignin recovery by two-stage concentrated and dilute sulphuric acid treatment, their properties and their depolymerization into low molecular mass aromatic fractions using homogeneous and heterogeneous Bronsted acidic ionic liquids as catalysts, is carried out. Correlation between the properties of RHs and recovered lignin were performed using destructive (CHNS, TGA, ICP-OES, etc.) and non-destructive (XRD, UV-Visible, FT-IR, and C-13 CP-MAS NMR) analytical techniques. It was observed that the recovered lignin was polysaccharides free and associated with dibenzodioxocin, spirodienone, and tricin type moieties with variable intensities. The effects of lignin structures showed a change of depolymerisation product pattern. [GRAPHICS] .
Keywords: Holocellulose; Homogeneous and heterogeneous catalysts; lignin; Rice husks

Designing an industrially viable bimetallic catalyst for the polyol synthesis - Kadam, Jyoti R.; Khan, Tufeil Sartaj; Dhepe, Paresh L. (New Journal of Chemistry, 2023)
Designing new catalysts for the hydrogenation of sugars is important since the conventional catalyst RANEY (R) Ni faces issues such as leaching, operation under severe conditions (similar to 100 bar H-2) to achieve better yields and formation of complexes of Ni with polyols. To overcome these issues and to have an industrially acceptable methodology, bimetallic catalysts with varying metal loadings (Ru = 1.5 and 2 wt% and Co = 1.5, 3, and 4 wt%) were synthesized in the current work and their hydrogenation activities were evaluated for the synthesis of sugar alcohols from various sugars. It was revealed that the nature of the support plays an important role in deciding the selectivity and activity of the catalyst and amongst all the supports, basic alumina showed the best activity due to its contribution to the ring opening of sugars. C5 and C6 sugars were successfully hydrogenated to their respective sugar alcohols under low H-2 pressures (15 bar) and it was observed that as compared to the monometallic (1.5)Ru/Al-Basic catalyst, the bimetallic (1.5)Ru(3)Co/Al-Basic catalyst showed enhancement in the activity by almost 1.5 times. The improvement in the activity is suggested to be due to (i) observance of the synergistic effect between the base metal (Ru) and the promoter metal (Co); (ii) effect of basicity of the support; and (iii) electronic effect of Ru and Co. Recyclability of the catalysts and their efficiency to hydrogenate higher concentration substrate solutions (10-20 wt%) make the overall process industrially attractive.

Industry-oriented method for the aqueous phase oxidation of crude 5-hydroxymethyl furfural (HMF) to 2,5-furandicarboxylic acid (FDCA) - Lokhande, Priya; Sonone, Kalyani; Dhepe, Paresh L. (New Journal of Chemistry, 2023)
Valorization of cellulose, hemicellulose, and lignin into value-added industrially relevant chemicals is important to achieve sustainability goals that various governments and industries have set. In view of this, the oxidative synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethyl furfural (HMF) as an analogous compound to terephthalic acid in the synthesis of PEF is interesting to researchers. Though advancements in the oxidation of HMF have been made, the efficient synthesis of HMF, its storage, and isolation are great challenges due to its instability under normal conditions. While purified HMF can be used to synthesize FDCA, it is imperative to use crude HMF for the synthesis of FDCA since several techno-economical studies reveal that the purification of HMF is the most cost-intensive step. Herein, we demonstrate the oxidation of crude HMF, synthesized in the laboratory to FDCA, using nonprecious-based mixed metal oxides in the aqueous medium in the presence of oxygen/air. Among various catalysts, Cu-Mn catalyst at 120 & DEG;C within 8 h in the presence of oxygen (10 bar) could yield 90% FDCA. This activity was comparable with that of the commercially available and well-studied Ru/C (5 wt%) catalyst (93% yield). In addition, the role of HMF purity, air as an oxidant, and the influence of temperature, pressure, and time is systematically studied. It is also demonstrated that FDCA formation proceeds via HMFCA and FFCA formation. The isolation of FDCA and its purity (>99%) is corroborated with various techniques such as NMR, IR, and HRMS.

Selective and robust Ru catalyst for the aqueous phase aerobic oxidation of furfural to 2-furoic acid - Lokhande, Priya; Dhepe, Paresh L. (ACS Applied Materials & Interfaces, 2023)
Synthesis of 2-furoic acid (FURA) via oxidation of furfural (FAL) is vital in evolving the biorefinery concept as FURA has numerous important applications in the pharmaceuticals and optic areas. Though few works on this reaction are done, those are marred with shortcomings such as the nonrecyclability of catalyst, dilute solutions, lower yields, or use of H2O2 as an oxidizing agent. Herein, we report catalytic aqueous phase oxidation of FAL to FURA using molecular oxygen as an oxidizing agent. For the synthesis of FURA, various catalysts with a combination of metal (Pt, Pd, Ru) and supports (carbon, Al2O3) were prepared and characterized by multiple techniques (X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS)). Oxidation of FAL carried out over 5 wt % Ru/C catalyst in the presence of Na2CO3 yielded 83% of FURA at 120 degrees C and 15 bar oxygen pressure. The catalyst could show potential for reusability as similar activity was achieved after subjecting the spent catalyst to mild reduction treatment (150 degrees C). Studies on the effects of temperature, pressure, and time could help accomplish enhanced yields of FURA. Additionally, learning about the effect of base (weak/strong/solid) revealed that due to the weak basicity of Na2CO3, higher yields could be achieved by maintaining approximately a pH of 11, which is optimal for suppressing side reactions. Under the given conditions, FURA is stable (>90%) and also adsorption studies divulge that it is immediately removed from the catalyst surface, and hence higher yields could be achieved in our catalytic system. Using the initial rates methodology, an activation energy of 21.91 kJ mol(-1) was derived and also a high turn over frequency (TOF) (85.9 h(-1)) was observed under optimized conditions.
Keywords: 2-furoic acid (FURA); Biomass conversion; furfural (FAL); heterogeneous catalyst; Oxidation; ruthenium on carbon etc

Lignocellulosic biomass analysis: acidic lignin recovery, characterisation, and depolymerisation - Singh, Sandip K.; Matsagar, Babasaheb M.; Dhepe, Paresh L. (Biomass Conversion and Biorefinery, 2024)
For the development of an effective lignocellulosic biomass conversion technology to biofuels and chemicals, the biomass composition analysis and their properties need to be characterised prior to biomass valorisation, including polysaccharide hydrolysis and lignin depolymerisation. In this work, a facile colorimetric titration method for the quantification of alpha-, beta-, and gamma-cellulose, pentosan, lignin, and silica percentages of wheat straw (WS) and two bagasse (BG I and II) samples was done. The result showed higher amounts of structural biopolymers (i.e. holocellulose and lignin (similar to 89.3%)) in BG compared to WS (81%) sample. Lignin recovery from BG (I and II) and WS samples was done by applying two-stage concentrated and dilute sulphuric acid hydrolysis, and maximum recovery (i.e. 21.5%; acid soluble +insoluble) of lignin obtained from BG II sample. Elemental and composition analysis results were represented substantial differences in lignin properties, including higher heat values (19.8 MJkg(-1)) of recovered lignin from BG II as well as high amounts of silica percentage from WS lignin. An intense Si-O-Si asymmetric stretching mode and/or C-O-C aliphatic aromatic ether (similar to 1100 cm(-1)) was characterised for lignin derived from WS. C-13 CP-MAS NMR exhibited variable intensities for dibenzodioxocin, spirodienone, and tricin moieties in recovered lignin samples. These lignin samples were processed for depolymerisation using homogeneous (1-methyl-3-(3-sulphopropyl)-imidazolium hydrogen sulphate) and heterogeneous (immobilised Bronsted acidic ionic liquid) catalysts to lower molar mass aromatic fractions and represented 89% and 92% organic solvent-soluble product yields respectively from WS-derived lignin.
Keywords: bagasse; Dibenzodioxocin; Holocellulose; Lignin depolymerisation; Spirodienone; Tricin; Wheat straw

Role of nitrogen doping in modulating ruthenium nanocatalysts for enhanced electrochemical hydrogen evolution reaction in alkaline medium - Korampattu, Lavanya; Barik, Sidharth; Pandikassala, Ajmal; Urkude, Rajashri R.; Kurungot, Sreekumar; Dhepe, Paresh L. (Chemistry of Materials, 2024)
Nitrogen doping has become a fundamental approach to enhance the catalytic performance of carbon materials across various applications. The introduction of nitrogen creates defects and active sites, promoting the formation of small metal particles and strengthening the metal-support interaction within carbon materials. However, the challenge lies in developing sustainable and cost-effective methods for synthesizing nitrogen-doped carbon materials. In this study, we present a sustainable approach for the synthesis of ruthenium on nitrogen-doped carbon catalysts (Ru-CCP) using chitosan as a nitrogen and carbon source. Unlike traditional methods, our process avoids the use of additional nitrogen precursors and templates, streamlining the synthesis while using a renewable resource. The synthesized material exhibits an exceptional performance in the electrochemical hydrogen evolution reaction (HER) in alkaline conditions by achieving a current density of 25 mA cm(-2) at an impressively low overpotential of 46 mV, outperforming Pt/C under similar conditions. The detailed studies on structural and electronic properties of the materials using X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and transmission electron microscopy (TEM) revealed that the remarkable catalytic activity is upheld by the unique interplay between Ru delta+ and surface nitrogen moieties, notably pyridinic and pyrrolic nitrogen. Here, we demonstrate the control of particle size and electronic environment around the metal atom via the interaction of nitrogen and unravel the role of nitrogen doping in tuning the catalytic performance. In addition, this work offers insights into efficient HER catalyst design and emphasizes the potential of biomass-derived materials like chitosan in advancing clean hydrogen production for renewable energy applications.

Ru/MgO-catalysed selective aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Lokhande, Priya; Dhepe, Paresh L.; Wilson, Karen; Lee, Adam F. (Australian Journal of Chemistry - an International Journal for Chemical Science, 2024)
Biomass valorisation through the selective oxidation of carbohydrate and lipid derivatives offers access to an array of platform chemicals through energy- and atom-efficient catalytic processes. Supported metal nanoparticles are promising catalysts for the aerobic selective oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA), but typically require strong liquid base to achieve high selectivity. Here, we explore the utility of MgO as a solid base support for the Ru-catalysed aerobic oxidation of HMF, obtaining 68% FDCA yield at 160°C and 1.5 MPa of O<span style="box-sizing: inherit; font-size: 11.25px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(0, 49, 60); font-family: "Open Sans", sans-serif; background-color: rgb(241, 250, 244);">2 using <1 mol-% metal.

Shell waste valorization to chemicals: methods and progress - Korampattu, Lavanya; Ghosh, Neha; Dhepe, Paresh L. (Green Chemistry, 2024)
In light of growing energy and resource demands, the conversion of biomass materials into diverse chemicals and fuels holds significant importance. This process enables the utilization of biomass as a valuable and renewable resource to meet these escalating needs. The current biomass valorization processes are largely based on plant-derived lignocellulosic biomass materials. Studying new genres of biomass materials and their value addition is highly desirable, and they would complement and expand the existing biorefinery system. Crustacean shell waste represents a highly potential bioresource that is composed of a set of useful chemicals, among which chitin, the amino polysaccharide, has come to the fore as a promising material for a plethora of applications. In terms of the abundance of biopolymers on Earth, cellulose is the most prevalent biopolymer, and chitin ranks as the second. The presence of biologically fixed nitrogen in the structure of chitin opens up new possibilities for making useful chemicals, notably nitrogen-containing chemicals, which are otherwise impossible to produce directly from lignocellulosic biomass. In the last two decades, several attempts have been made by researchers in this area to convert chitin and its derivatives into valuable chemicals. This review comprehensively summarizes the transformation of the chitin fraction from shell waste to various chemicals through different thermo-catalytic processes and appraises the advancements in this area. The effect of various catalytic systems on chitin biomass valorization processes and the challenges and opportunities allied to this are discussed. This review summarises the thermo-catalytic processes converting chitin from shell waste into diverse chemicals and reviews the advances, catalytic systems, and associated challenges.

Chitosan-derived carbon supported ruthenium catalyst for efficient hydrogenation of levulinic acid to γ-valerolactone - Korampattu, Lavanya; Dhepe, Paresh L. (Sustainable Energy & Fuels, 2025)
The transition from fossil fuels to sustainable energy and chemical production relies heavily on efficient biomass valorization. Levulinic acid (LA), a key platform chemical from lignocellulosic biomass, serves as a versatile precursor for valuable chemicals like gamma-valerolactone (GVL), a promising green solvent, fuel additive, and polymer precursor. While ruthenium-based catalysts are effective for LA hydrogenation, conventional systems like Ru/C often suffer from metal leaching and deactivation due to weak metal-support interactions. Current approaches to improve stability, such as using nitrogen-doped carbon supports, involve complex synthesis and synthetic nitrogen precursors. Addressing these limitations, we present a facile and sustainable strategy for synthesizing a robust ruthenium catalyst by directly pyrolyzing marine biomass-derived chitosan to form a self-nitrogen-doped carbon support. This catalyst exhibited superior stability and excellent recyclability in the aqueous-phase hydrogenation of LA to GVL, surpassing conventional Ru/C while maintaining activity comparable to that of leading Ru catalysts supported on N-doped carbon. Unlike other N-doped carbon supports, our method avoids synthetic N-dopants and tedious procedures, making it inherently more sustainable. Detailed characterization via XPS and H2-TPR revealed strong metal-support interactions, facilitated by intrinsic nitrogen functionalities, effectively stabilizing the ruthenium species. This study also identifies the critical role of graphitic and pyridinic nitrogen species in controlling catalytic activity and elucidates the importance of optimizing nitrogen species and content in tailoring chitosan-derived supports. The proposed mechanism describes how Ru-N centers activate hydrogen and LA, with basic nitrogen sites aiding the dehydration step to GVL. Overall, this work features the potential of chitosan derived carbon as a sustainable and tunable support for efficient biomass hydrogenation catalysts and offers fundamental insights into the role of nitrogen doping in tailoring catalytic performance.

Continuous flow hydrodeoxygenation of lignin-derived guaiacol to cyclohexanol over durable Al2O3 hollow fiber supported co catalyst - Singh, Dheerendra; Jogdand, Shunottara M.; Devi, R. Nandini; Dhepe, Paresh L. (ChemCatChem, 2025)
The drive to decarbonize the chemical, oil, and gas industries through use of bio-derived resources is intensifying. This study focuses on converting lignin-derived phenolic compounds into cyclohexanol, a precursor for adipic acid production. The alumina hollow fiber supported cobalt catalyst (5Co/AHF@capillary) prepared by capillary action method was found to consist cobalt in both metallic and +delta oxidation states. Initial tests in a batch-mode reactor showed promising results, with 5Co/AHF@capillary catalyst demonstrating catalytic activity comparable to Ru/Al2O3 systems (225 degrees C, 1 MPa H-2, 4 h), achieving similar to 86% cyclohexanol yield in guaiacol hydrodeoxygenation reactions. The catalytic system was then adapted for continuous flow reactors under milder conditions (300 degrees C, 2.5 MPa H-2, 18 mL min(-1)), resulting in 83% guaiacol conversion and 74% cyclohexanol yield. The durability of the catalyst was checked for >80 h and results claim that catalyst was active in yielding consistent results. The roles of catalyst preparation method, hydrogen pressure, solvent, WHSV were thoroughly checked and discussed.
Keywords: biomass valorization; Carbon; Co/Al2O3; Cyclohexanol; lignin

Experimental investigation and lumped kinetic modeling studies for upcycling of polyolefins - Kavade, Omkar G.; Dhepe, Paresh L.; Devi, Nandini R.; Vasireddy, Satyam Naidu (Journal of the Indian Chemical Society, 2025)
The present work discusses on comparative kinetic analysis of the pyrolysis of polypropylene (PP), high-density polyethylene (HDPE), and low-density polyethylene (LDPE) using sophisticated lumped models. Unlike many previous studies that focused on single-polymer kinetic models or employed simplified reaction schemes, this study develops an enhanced multistep reaction network that explicitly considers both primary decomposition and secondary cracking pathways, thereby improving the accuracy of product distribution predictions. By integrating this detailed reaction framework with a robust nonlinear regression approach using LSQNONLIN and ODE45 solvers in MATLAB, the study achieved greater accuracy in estimating kinetic parameters than traditional curve-fitting methods. The findings reveal that HDPE exhibits the highest activation energy (222.97 kJ mol(-1)), indicating it is more thermally stable than LDPE (193.44 kJ mol(-1)) and PP (62.16 kJ mol(-1)). One of the highlights of the present work is that lower pyrolysis temperature (400 degrees C) is found to be optimum for liquid yield by reducing secondary cracking, which aligns with the sustainable fuel production principles. The study also emphasizes on the limitations of previous lumped models that overlooked wax decomposition pathways, which are crucial for optimizing the hydrocarbon distribution. Future research should investigate catalytic interventions and reactor design modifications to enhance the product selectivity and scalability. This study offers a more comprehensive kinetic framework for advancing the valorization of plastic waste through pyrolysis, aiding the development of efficient waste-to-fuel conversion strategies.
Keywords: Lumped kinetic modeling; Plastic pyrolysis; Rate constants; Reaction pathways; Secondary cracking reactions; Temperature-dependent product distributions